Użyteczność stosowania pojęcia „rodzina normalna” – z perspektywy pomocy psychologiczno-pedagogicznej - Gulczyńska, Anna (Studia Edukacyjne, 2017)
The article gives an insight into the meaning of the term “normal family” and the potential implications of its use. The modernist and the postmodernist approaches presented are supposed to contribute to a reflection on the current usefulness of this term, i.e. to what extent it describes the family and work with it. The use of the terms: norm and normal is mistaken for objectivism and neutrality. It is therefore worth considering in the context of narration about the family terms such as: healthy, functional, successful, adapting, and when using the term norm or standard, to add criteria of its description. The article first presents selected definitions of norms, then the approaches to the normal family, and the resultant conclusions. Further on the article indicates the results of preliminary analyses of statements made by students, showing their ways of defining the notion of a “normal family”. Subsequently a summary is made from the perspective of both modernism and postmodernism.